2018
DOI: 10.4066/biomedicalresearch.29-17-2029
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C and cystatin C/albumin ratio for the evaluation of liver function in patients with cirrhosis

Abstract: Purpose: The aim of this study is to analyze the serum cystatin C (Cys C) and cystatin C/albumin (Alb) ratio in patients with cirrhosis and evaluate the role of serum Cys C in the evaluation of liver function. Methods: The liver function of patients was graded according to the Child-Pugh Score. According to the serum Cys C levels (determined with particle-enhanced immunonephelometric assay), the patients were divided into two groups: the high Cys C level group and normal Cys C level group. The correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…[13] Other studies have indicated that serum albumin can predict the presence of EVs. [17] Based on the better correlation between the CAR and the CTP score compared to CysC, [10] we investigated the potential of CAR for early diagnosis of EVs in patients with cirrhosis, aiming to identify a noninvasive diagnostic method as EGD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] Other studies have indicated that serum albumin can predict the presence of EVs. [17] Based on the better correlation between the CAR and the CTP score compared to CysC, [10] we investigated the potential of CAR for early diagnosis of EVs in patients with cirrhosis, aiming to identify a noninvasive diagnostic method as EGD.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Previous investigations have demonstrated that both CysC and the CysC/Albumin ratio (CAR) are positively correlated with CTP score and grading, with CAR showing better correlation with liver function compared to CysC alone. [10] However, there is currently a lack of research on the association between CAR and esophageal varices (EVs) in patients with liver cirrhosis. Thus, this study aims to analyze the relationship between CAR and EVs in cirrhotic patients, with the goal of further evaluating the potential role of CAR in the early diagnosis of EVs in cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation